Myelodysplastic Syndrome Progression to Acute Myeloid Leukemia in a Cat FeLV Seroreactive - Silva, Tatiane de Paula; Zanfagnini, Leticia Gomes; de Oliveira, Alana Cristina; Ribeiro, Diefrey Campos; de Oliveira, Leticia Gonçalves; Silva, Paulo Ricardo Rosa; Messias, Cassio Toledo; Pacheco, Acácio Duarte (Acta Scientiae Veterinariae, 2022)
Background: Acute myeloid leukemia (AML) is a group of non-lymphoid hematological tumors characterized by aberrant proliferation and/or decreased apoptosis of a clone of non-mature cells, resulting in the accumulation of immature blast cells in the bone marrow and peripheral blood. It is considered rare, as it represents 10% of neoplasms of hematopoietic origin. However, it is known that felines seroreactive for FIV and FeLV are more predisposed and reports of this type of leukemia in cats in the literature are scarce. Thus, the objective of this study was to evaluate the blood and bone marrow of a cat seroreactive for FeLV that presented with myelodysplastic syndrome that progressed to acute myeloid leukemia. Case: A 6-year-old male mixed-breed cat, neutered, seroreactive for FeLV, showed apathy, weight loss, and pale mucous membranes. Initial peripheral blood smear evaluation revealed hypochromic normocytic anemia, leukopenia, neutropenia, lymphopenia, and thrombocytosis with many macropackets and giant platelets. Based on this blood picture, a long-spectrum antimicrobial therapy with amoxicillin and clavulanate [Clavulin® BD - 25 mg/kg, every 12 h] was started. Granulocyte colony stimulating factor used filgrastim (rHu G-CSF) [Fiprina® - 5 µg/kg, SC, every 48 h] and appetite stimulant mirtazapine [Mirtz® - 2 mg/cat, orally, every 48 h] were used to correct leukopenia and nutritional status, respectively. Follow-up blood smear evaluation on the 30th day showed persistence of the hematological changes noticed earlier. A bone marrow puncture was performed, and immunosuppressive therapy with prednisolone [Predsim® - 4 mg/kg, orally, every 24 h] was initiated. The aspirated material showed increased cellularity for age, decreased myeloid:erythroid ratio, and 39.8% of blasts of myeloid origin. An average of 17.7 megakaryocytes were observed per field (10x magnification). Bone marrow cytological evaluation suggested acute myeloid leukemia with dysmegakaryocytopoiesis. After the diagnosis, the examinations were repeated monthly, and there was still intense leukopenia. However, in view of the stable clinical status and leukopenia with neutropenia, treatment for leukemia was not instituted and only supportive treatment was administered when necessary. Eight months after the diagnosis, clinical status had worsened, and unlike the earlier hemograms, global leukocyte count had increased with predominant lymphocytosis (95% of the total leukocytes) with atypical lymphocytes. The cat died a few days later. Discussion: Bone marrow evaluation is indicated when peripheral blood cell abnormalities are present and cannot be explained in the context of the clinical history. In the present report, the bone marrow aspirate was hypercellular (cellularity above 75%); however, intense leukopenia was observed in the peripheral blood. In myelodysplastic syndromes, it is common for the bone marrow to be normal to hypercellular, which occurs when there is a greater production of myeloid or erythroid cell lines in response to the loss, destruction, or consumption of cells. Despite this, cytopenias may be present in the peripheral blood, since the defective cells undergo apoptosis and die before being released into the circulation, characterizing inefficient hematopoiesis. The diagnosis of acute leukemia comprises a variety of hematopoietic neoplasms that are complex and unique. Each acute leukemia subtype has defining characteristics that affect the prognosis and treatment of each animal. Keywords: tumours, myeloid neoplasm, SMD, LMA, bone marrow cytology, feline.